Compact and reflective light-sheet microscopy for long-term imaging of living embryos - Moretti, Bruno (2020)
The development of light-sheet fluorescence microscopy has been a revolution for developmental biology as it allows long-term imaging during embryonic development. An important reason behind the quick adoption has been the availability of open hardware alternatives. In this work, we present a robust and compact version of a light-sheet fluorescence microscope that is easy to assemble and requires little to no maintenance. An important aspect of the design is that the illumination unit consists of reflective elements, thereby reducing chromatic aberrations an order of magnitude as compared to refractive counterparts.